상업적 이용 목적의 유전자원 접근 및 이익배분에 대한 고찰 - 고재종; Jae-jong Koh (지식재산연구, 2015)
유전자원에 관한 국제적인 논의는 지구환경의 보전을 위한「기후변동에 관한 국제연합 기본협약」과 지구상의 유전자원의 보전을 위한「생물다양성협약」부터 시작되었다고 할 수 있다. 그런데 유전자원의 보존 및 지속적인 이용을 위하여 자원국에게 유전자원의 주권적 권리를 인정하고, 이용국의 유전자원의 접근·이용에 따라 발생한 이익에 대해서도 배분할 것을 요구하였다. 이는 자원국과 이용국 모두에게 이익을 어떻게 배분할 것인가는 매우 중요한 문제가 되고 있다. 따라서 「생물다양성협약」에 이익은‘공정 하고 형평하게’배분하여야 한다는 원칙을 규정하였고, 이와 관련한 다양한 원칙을 제시하였다. 하지만, 실제로는 자원국과 이용국 간의 계약에 의하여 이익배당의 문제를 해결하고 있다. 나아가, 이와 관련된 정보도 충분하지 않은 실정이다. 이에 본 논문은 유전자원의 접근·이용에 따른 이익배분의 문제와 관련하여 국제적인 흐름 및 각국의 동향과 더불어 실제의 사례를 통하여 이익배분의 문제를 어떻게 처리하고 있는지를 검토하여 향후 우리나라의 기업이 유전자원의 접근·이용과 관련하여 어떻게 대처하여야 하는지 그 시사점을 얻고자 하였다. It is commonly accepted that discussing on the genetic resources and traditional knowledge associated with genetic resources is started to establish the United Nations Framework Convention on Climate Change(UNFCCC) and the Convention on Biological Diversity(CBD). By the above two international agreement, a providing party of such resources is admitted to the sovereign rights over natural resources for the conservation of those resources and the sustainable use of those components. And It is demanded that benefits arising from the access and use of those resources benefits as well as subsequent applications and commercialization shall be shared in a fair and equitable way between the parties. But in fact, these problems on the sharing of benefits is solved to the contracts between a providing party and the other party. Furthermore, it is not sufficient to know the information of the related on those problems. Therefore, I will study on the following problems about the sharing of the benefits as the result of the access and use of genetic resources. Firstly, I will inquiry into the international flow and the preparation conditions for each country. Secondly, I will examine how the problems are solved through entering into the actual contracts. Lastly, I will suggest on the solving methods on the problems of sharing of benefits about the access and use of the genetic resources and traditional knowledge related on the those resources.